Socio-Economic Benefits of Community Forest - Subedi, Bed Kumari (Rural Development Journal, 2017)
Nepal’s community forestry has become an example of progressive legislation and policies in the decentralization of forest management. It has attracted international attention because in Nepal, decentralization is linked with emerging issues sustainable forest management, forest governance, policy advocacy, equity, gender, poverty and the role of civil society in community forestry. The text examines the socio-economic and environmental benefits of community forestry on the local community. In the study area, which includes 240 member households, a sample of 60 households (Forest User Groups - FUGs) was selected through random probability sampling. The community forestry initiative contributes to the development of local human resources and enhances rural livelihoods. It empowers people by fostering team building, group dynamics, and self-motivation in community development. Both direct and indirect benefits from community forestry have significantly impacted the social life of the people in the study area. The primary economic activities of the FUGs include agriculture, livestock farming, and various home-based industries. Industries such as iron-based, furniture, and bamboo-based rely on the forest for raw materials, indicating the forest's role in the local economy and its contribution to additional income. The research also highlights the forest's environmental aspect, noting the effective conservation of biodiversity through various activities.